ENGLISH–DEVELOPING MUSLIM AND NON-MUSLIM SOCIAL RELATIONS: ANALYSIS OF ISLAMIC TEACHINGS & ITS IMPACT - Hafiza Farhat; Muhammad Riaz Mahmood (دی اسکالر)
Globalization has brought the nations of the world closer, but clashes between societies are still underway. The need of the hour is building bridges between various cultures and religious dogmas. It is an historical fact that Islam has a vision to respect other religions. Religious tolerance is the exemplary symbol of all Muslim communities. Islam has given the right to express the faith to all the followers of different religions. The issue of living together peacefully is important for the Muslim migrants and for the hosting western states too. Both must coexist in the world and one needs the other. Because of the international menace of extremism and terrorism over the past decade, many serious rifts have developed and being promoted between the Muslims and Non-Muslims. Hence, building bridges between them is essential. The present research article discusses some key issues which Muslims face when they settle in the west. It is meant to broaden the minds of the Muslim community in their day-to-day dealings with the people who do not share their faith so that the world may turn into a hub of peace and harmony.